Is the Peripheral Zone Thickness an Indicator of a Learning Curve in Bipolar Transurethral Plasma Enucleation of the Prostate?—A Single Center Cohort Study - Wang, Qihua; Alshayyah, Rami; He, Yi; Wen, Lijie; Yu, Yang; Yang, Bo (Frontiers in Surgery, 2022)
Background We conducted this cohort study to assess the differences in the learning curve of bipolar transurethral plasma enucleation of the prostate (B-TUEP) associated with prostatic peripheral zone thickness (PZT) under MRI quantitative measurement. Methods 60 patients with benign prostatic hyperplasia (BPH) were involved. PZT are defined as “Thin” (<7 mm), “Thick” (>10 mm) and “Medium” (in between), with 20 patients in each group. Based on learning stages, it was defined as Group 1 (No.1-20), Group 2 (No.21-40) and Group 3 (No.41-60). We measured parameters of prostate with MRI, such as PZT, transitional zone thickness (TZT), etc. A learner with no experience in enucleation perform the operations. Statistical analyze were performed to compare the differences. Pearson correlation analysis and multiple linear regression analysis evaluated relationship between characteristics of patients. P <0.05 was deemed statistically significant. Results One-Way ANOVA revealed different enucleation efficiency (0.811±0.18 vs 0.748±0.14 vs 0.634±0.16), prostate volume (58.9±15.33 vs 57.3±15.58 vs 46.6±14.10) and thickness of transition zone (44.45±7.60 vs 42.45±6.08 vs 34.78±6.04) among Thin, Medium and Thick groups. The enucleation efficiency is different between groups divided by learning stages (Group 1 vs Group 3, 0.658 vs 0.783; Group 2 vs Group 3, 0.751 vs 0.783). Pearson correlation analysis reveals that PZT was negatively correlated with prostate volume (r=-0.427), resection weight (r=-0.35), enucleation efficiency (r=-0.445) and TZT (r=-0.533), and was positively correlated with Q-max (r=0.301) and bladder outlet obstruction index (BOOI) (r=0.388). The regression coefficients of PZT, TZT, prostate volume and Q-max were -0.012, 0.008, 0.007 and 0.013, respectively (all P < 0.05). Conclusion Lower PZT is independent related to higher enucleation efficiency, larger adenoma and higher TZT. PZT may be an important factor on the learning curve of B-TUEP. Higher TZT, prostate volume and Q-max may also relate to higher enucleation efficiency. For B-TUEP learners, it seems easier to perform when the PZT is low, though the capsule perforation should be more careful. Besides, the capsule plane should be maintained more attentively if the PZT is high.